Are girls more ambitious than boys? : vocational interests partly explain gender differences in occupational aspirations - Wicht, Alexandra [Verfasser]; Miyamoto, Ai [Verfasser]; Lechner, Clemens M. [Verfasser] (My University, 2022)
"Previous research suggests that girls have higher occupational aspirations than boys before entering the labor market. We investigate whether this gender gap in occupational aspirations generalizes to secondary school students in Germany and illuminate the possible mechanisms behind these purported gender differences. For this purpose, we used a large and representative sample of ninth graders (N = 10,743) from the German National Educational Panel Study. Adolescents’ occupational aspirations were coded on the International Socio-Economic Index of Occupational Status (ISEI) according to the socioeconomic status of the aspired occupation. Results showed that girls’ occupational aspirations were 6.5 ISEI points higher than boys’ (Cohen’s d = .36). Mediation analyses further revealed that gender differences in vocational interest could explain one-half of the gender gap in occupational aspirations. This suggests that girls’ higher occupational aspirations reflect their specific vocational interests rather than a general striving for higher status and prestige compared to boys." (Authors' abstract ; BIBB-Doku)
Keywords: G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.3.2.2 Übergänge; I 2.1 Deutschland; 370; 300; Berufswunsch; Berufsneigung; Berufsinteresse; Nationales Bildungspanel; Geschlechterdifferenz; Geschlechterverteilung; Sekundarstufe I; Bundesrepublik Deutschland